THE FACTORS AFFECTING THE OCCURRATION OF FRAUD IN PHARMACEUTICAL COMPANIES IN NORTH SUMATERA - Albar, Ahmad Riski (Asosiasi Dosen Akuntansi Indonesia, 2019)
The purpose of this study aims to determine and analyse the effect of Pressure, Opportunity, Rationalization, Capability, Greed and Exposure both simultaneously and partially on Fraud on pharmaceutical companies in North Sumatra. The study population is 154 employees of pharmaceutical companies. The sample was selected using a purposive sampling method that produced 61 employees as sample respondents. Data analysis methods in this study are descriptive statistics, multiple regression analysis (Multiple Regression Analysis), and to find out the regression coefficients using the Ordinary Least Square (OLS) method, classical assumption test, hypothesis testing. The data of this study were processed using the Statistical Package for Social Science (SPSS) program 21. The results of this study indicate that Pressure has a positive and significant impact on Fraud, Opportunity has a positive and significant effect on Fraud, Rationalization has a positive and significant effect on Fraud, Capability has a positive and significant effect on Fraud, Greed has a negative and insignificant effect on Fraud, and Exposure has a positive effect and not significant to Fraud on ??pharmaceutical companies in North Sumatra.